Indoor Air Quality Evaluation of guests’ rooms in hotel building: a Case Study of Turówka Hotel - Borowski, Marek; Zwolińska, Klaudia; Ryba, Bernadetta (CLIMA 2022 conference, 2022)
The advancement of civilizations and the development of society increase the amount of time that a person spends indoors. Currently, people spend up to 80-90% of their lives in buildings, which is why it is so important to ensure proper thermal conditions and high indoor air quality. Air exchange in the rooms is a necessary process for comfort due to the concentration of oxygen and carbon dioxide and the removal of heat and pollutants. The presence of users is a source of pollution in the form of carbon dioxide and heat emitted. An insufficient supply of fresh air may lead to the increase of dioxide concentration to levels that disturb the proper functioning of the body. Installations in hotel buildings must be designed and operated in such a way as to ensure high comfort and meet the high requirements of customers in terms of the internal environment, safety, and reliability of the system. The study aimed to analyse air quality and thermal comfort in hotel rooms. The research was conducted in a historic hotel located in southern Poland. The building consists of four above-ground stories and the basement. The building has 50 double rooms, a conference room for 40 people, and a restaurant with 90 seats for guests. Temperature, humidity, and carbon dioxide concentrations were measured in the rooms. The analysis was conducted based on data from the daily and weekly cycles and included the influence of external factors. Measurements in hotel rooms were carried out continuously with a sampling period of 1 minute, both in the presence and absence of guests. The paper presents an analysis of the variability of air parameters in a daily and weekly cycle and the influence of external factors on the measured values. On this basis, it will be possible to assess the air quality inside hotel rooms and propose solutions to improve internal conditions.